MCF-7 Human Breast Cancer Cells Form Differentiated Microtissues in Scaffold-Free Hydrogels - Vantangoli, Marguerite M.; Madnick, Samantha J.; Huse, Susan M.; Weston, Paula; Boekelheide, Kim (PLOS ONE, 2015)
Three-dimensional (3D) cultures are increasing in use because of their ability to represent in vivo human physiology when compared to monolayer two-dimensional (2D) cultures. When grown in 3D using scaffold-free agarose hydrogels, MCF-7 human breast cancer cells self-organize to form directionally-oriented microtissues that contain a luminal space, reminiscent of the in vivo structure of the mammary gland. When compared to MCF-7 cells cultured in 2D monolayer culture, MCF-7 microtissues exhibit increased mRNA expression of luminal epithelial markers keratin 8 and keratin 19 and decreased expression of basal marker keratin 14 and the mesenchymal marker vimentin. These 3D MCF-7 microtissues remain responsive to estrogens, as demonstrated by induction of known estrogen target mRNAs following exposure to 17β-estradiol. Culture of MCF-7 cells in scaffold-free conditions allows for the formation of more differentiated, estrogen-responsive structures that are a more relevant system for evaluation of estrogenic compounds than traditional 2D models.